An algebra problem by Anish Roy

Algebra Level 3

True or False?

If a a , b b , and c c are positive real numbers such that a a + 1 + b b + 1 + c c + 1 = 1 \dfrac a{a+1} + \dfrac b{b+1} + \dfrac c{c+1} = 1 , then the maximum value of a b c abc is 1 8 \dfrac18 .

True False

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Alex Delhumeau
Jun 4, 2017

Manipulation yields c = 1 a b 2 a b + a + b c = \frac{1-ab}{2ab+a+b} . Thus a b c = ( a b ) ( 1 a b ) 2 a b + a + b abc = \frac{(ab)(1-ab)}{2ab+a+b} .

After this substitution, the question can now be interpreted as asking for the maximum value of f ( x , y ) = x y ( 1 x y ) 2 x y + x + y f(x,y) = \frac{xy(1-xy)}{2xy+x+y} over real x , y > 0 x,y>0 .

Clearly, m a x ( f ( x , y ) ) max(f(x,y)) will occur at the point where x = 0 \frac{\partial}{\partial x}=0 and y = 0 \frac{\partial}{\partial y}=0 . To find this point, we solve x = y 2 ( x + 1 ) ( x + 2 x y 1 ) ( 2 x y + x + y ) 2 \frac{\partial}{\partial x} = \frac{-y^2(x+1)(x+2xy-1)}{(2xy+x+y)^2} y = x 2 ( y + 1 ) ( y + 2 x y 1 ) ( 2 x y + x + y ) 2 \frac{\partial}{\partial y} = \frac{-x^2(y+1)(y+2xy-1)}{(2xy+x+y)^2}

Notice now since x , y > 0 x,y>0 , we must have 2 x y + x 1 = 0 2xy+x-1=0 and 2 x y + y 1 = 0 2xy+y-1=0 .

Therefore, x = y x=y as a result of 2 x y + x 1 ( 2 x y + y 1 ) = 0 ( 0 ) x y = 0 2xy+x-1-(2xy+y-1)=0-(0) \Rightarrow x-y =0 , meaning that we can solve directly 2 x 2 + x 1 = 0 2x^2+x-1=0 x = 1 2 , 1 x=\frac{1}{2}, -1 , with 1 < 0 -1<0 rejected, leaves only x = 0.5 x=0.5 .

Hence, calculating the maximum value of a b c = ( x y ) ( 1 x y ) 2 x y + x + y = 0.5 0.5 ( 1 0.5 0.5 ) 2 0.5 0.5 + 0.5 0.5 = 1 8 . abc = \frac{(xy)(1-xy)}{2xy+x+y} = \frac{0.5*0.5*(1-0.5*0.5)}{2*0.5*0.5+0.5*0.5} = \boxed{\frac{1}{8}}. The statement is T R U E \large{TRUE} .

i did it by AM -GM -HM

sam dave - 3 years, 11 months ago

Log in to reply

Please post your solution! I bet it would be more elegant than old school calculus.

William Nathanael Supriadi - 3 years, 11 months ago

Log in to reply

how can i upload a solution(like i solved it in my notebook ,but dont know how to upload its picture. ) ? actually i ticked false , so i am not having an option to upload my answer

sam dave - 3 years, 11 months ago

Log in to reply

@Sam Dave Just take a photo and upload it here. Or, if you have time, try to learn the LaTeX.

William Nathanael Supriadi - 3 years, 10 months ago

This is a very usual try, using calculus to solve any question regarding maximum and minimum. However, can you do it via AM-GM-HM? I can't Moreover, how do you know that it is maximum and not minimum?

William Nathanael Supriadi - 3 years, 12 months ago

Log in to reply

You use the Second Partials Test to show that it is a maximum and not a minimum:

x x = 2 x 2 ( y + 1 ) 2 ( 2 x y + x + y ) 3 \frac{\partial}{\partial x}\frac{\partial}{\partial x} = -\frac{2x^2(y+1)^2}{(2xy+x+y)^3} y y = 2 y 2 ( x + 1 ) 2 ( 2 x y + x + y ) 3 \frac{\partial}{\partial y}\frac{\partial}{\partial y} = -\frac{2y^2(x+1)^2}{(2xy+x+y)^3} y x = 2 x y ( x + 1 ) ( y + 1 ) ( 2 x y + x + y 1 ) ( 2 x y + x + y ) 3 \frac{\partial}{\partial y}\frac{\partial}{\partial x} = -\frac{2xy(x+1)(y+1)(2xy+x+y-1)}{(2xy+x+y)^3}

Evaluating each of these at x , y = 1 2 x,y=\frac{1}{2} , we find that f x x ( 0.5 , 0.5 ) = f y y ( 0.5 , 0.5 ) = 1 3 f_{xx}(0.5,0.5)=f_{yy}(0.5,0.5)=-\frac{1}{3} f x y ( 0.5 , 0.5 ) = 1 6 f_{xy}(0.5,0.5)=-\frac{1}{6} leads to f x x ( 0.5 , 0.5 ) f y y ( 0.5 , 0.5 ) ( f x y ( 0.5 , 0.5 ) ) 2 = f_{xx}(0.5,0.5)*f_{yy}(0.5,0.5)-(f_{xy}(0.5,0.5))^2= 1 3 ( 1 3 ) ( 1 6 ) 2 = -\frac{1}{3} * (-\frac{1}{3}) - (-\frac{1}{6})^2 = 1 9 1 36 = \frac{1}{9}-\frac{1}{36}= 1 12 > 0 \frac{1}{12}>0

f ( 0.5 , 0.5 ) \Rightarrow f(0.5,0.5) is not a saddle point .

Therefore, since f x x ( 0.5 , 0.5 ) = 1 3 < 0 f_{xx}(0.5,0.5)=-\frac{1}{3}<0 , ( 0.5 , 0.5 ) (0.5,0.5) must be a local maximum of f ( x , y ) f(x,y) .

As for whether there exists a quick and clever way to use inequalities for this problem, you should ask @Anish Roy .

Alex Delhumeau - 3 years, 12 months ago

Log in to reply

Thanks! My calculus has not reached that level though :( I just assumed that a, b, and c are all equal and try if they are not. And I get that if they are not equal, then the value is less than 1/8. Lol.

William Nathanael Supriadi - 3 years, 12 months ago
Anish Roy
Aug 15, 2017

This is equivalent to a ( 1 + b ) ( 1 + c ) = ( 1 + a ) ( 1 + b ) ( 1 + c ) . \sum a(1 + b)(1 + c) = (1 + a)(1 + b)(1 + c). This simplifies to a b + b c + c a + 2 a b c = 1 ab + bc + ca + 2abc = 1 Using AM-GM inequality, we have 1 = a b + b c + c a + 2 a b c 4 ( a b b c c a 2 a b c ) 1 / 4 1 = ab + bc + ca + 2abc ≥ 4(ab · bc · ca · 2abc)^{1/4} Simplificaton gives a b c 1 8 abc ≤ \frac{1}{8}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...